1993
DOI: 10.1103/physrevb.48.2400
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy positron diffraction from the (110) surfaces of GaAs and InP

Abstract: The intensities of 16 nonequivalent beams of normally incident positrons difFracted from the (110) surfaces of GaAs and InP are reported. The sample temperature was approximately 110 K. The intensities were measured over the energy range 30 eV~E(200 eV. The atomic geometries of GaAs(110) and InP(110) were extracted from these intensities via their comparison with the predictions of a multiplescattering model using the criterion of minimization of the x-ray R factor. The best-fit surface geometries resulting fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…The second triumph of Karl's positron diffraction work was that he was able to make more precise determinations of the surface structure of the compound semiconductors than were possible using electron diffraction [55][56][57][58][59][60][61][62] (see Fig. 15).…”
Section: Positron Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second triumph of Karl's positron diffraction work was that he was able to make more precise determinations of the surface structure of the compound semiconductors than were possible using electron diffraction [55][56][57][58][59][60][61][62] (see Fig. 15).…”
Section: Positron Diffractionmentioning
confidence: 99%
“…15. Positron diffraction pattern from a GaAs surface (left) [61] and CdTe (right) [62]. one could easily see with the naked eye if you squint.…”
Section: The Positron Reemission Microscopementioning
confidence: 99%
“…They developed an electrostatic slow-positron beam with a radioisotope (RI) source emitting positrons through β + -decay. The Brandeis group also demonstrated that in LEPD, experimental intensity profiles were more closely reproduced by the dynamical diffraction theory than in LEED [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41] Chen et al applied LEPD to GaAs and InP (110) surfaces, and showed that LEPD can more precisely specify the surface structure than LEED alone. 40 More precise studies of other ordered multi-component surfaces are expected.…”
Section: ·2 Low-energy Positron Diffraction (Lepd)mentioning
confidence: 99%